The Investigation of the Curing Reaction of Epoxidized Soybean Oil for Engineered Stone Application - Nguyen, Thi Thuy; Vu, Minh Duc; Nguyen, Thanh Liem (Old Journal, 2018)
Methylhexahydrophthalic anhydride (MHHPA) is used as the hot curing agent for epoxidized soybean oil with the presence of methyl imidazone (NMI). Effect of MHHPA, NMI, glycerine content and temperature on the hardening process were studied through the peak exothermic temperature of curing reaction. Moreover, differential scanning calorimetry analysis (DSC) was used to calculate a curing degree over time for epoxidized soybean oil-MHHPA system with the presence of NMI and glycerine. The obtained optimal conditions (Nepoxy /ΠΜΗΗΡΑ: 1.05/1; NMI: 2% (MDDN-E + MMHHPA); glycerine: 1.5% (MDEN-E + ΜΜΗΗΡΑ); 165°C, 40 minutes) was used for manufacturing the engineered stone. The results of characterizing of this stone showed that this study could open up the new pathway of replacing a hazardous unsaturated polyester resin with the environment-friendly epoxidized soybean oil in manufacturing the engineered stone.